O corpo na obra Ideias II de Husserl: esquecimento, sensações, ponto-zero. - Sousa, Leandro Righi de (2016)
The present study aims to present the general way in which Husserl understand the meaning of body as body-live from the bias of the sensations as well as the general sense of the body as zero-point (Nullpunkt), positioning this study from paragraphs §36-37 and §41 of the work Ideas II. In the first chapter we present the historical and philosophical reasons for the theme investigation, the etymological and philosophical origins of the term Leib and general aspects of the "body" in Ideas II work. In a second time, we drove a study on the constitution of the body as the body alive from the bias of sensations. In the third chapter of this work, we study the meaning of zero-point (Nullpunkt) body and the way the body from its zero (Null) position is originally the show look of things (Ding).